2020
DOI: 10.3390/life10100233
|View full text |Cite
|
Sign up to set email alerts
|

The Contractile Phenotype of Skeletal Muscle in TRPV1 Knockout Mice Is Gender-Specific and Exercise-Dependent

Abstract: The transient receptor potential vanilloid 1 (TRPV1) belongs to the transient receptor potential superfamily of sensory receptors. TRPV1 is a non-selective cation channel permeable to Ca2+ that is capable of detecting noxious heat temperature and acidosis. In skeletal muscles, TRPV1 operates as a reticular Ca2+-leak channel and several TRPV1 mutations have been associated with two muscle disorders: malignant hyperthermia (MH) and exertional heat stroke (EHS). Although TRPV1−/− mice have been available since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Interestingly, for the force transducer platform, we found that the tetanic-to-twitch ratio was significantly higher in human muscle compared to C2C12 muscle constructs (unpaired t-test, p < 0.05). We are uncertain about the relevance of this finding, but it is likely an intrinsic feature related to the species since gender-specific differences have been found for this parameter in native mouse muscles ( Lafoux et al, 2020 ). Of note, this parameter is independent of CSA and provides a functional measurement that could be used to compare different studies regardless of the construct size or platform used.…”
Section: Contractile Force Data Analysismentioning
confidence: 93%
“…Interestingly, for the force transducer platform, we found that the tetanic-to-twitch ratio was significantly higher in human muscle compared to C2C12 muscle constructs (unpaired t-test, p < 0.05). We are uncertain about the relevance of this finding, but it is likely an intrinsic feature related to the species since gender-specific differences have been found for this parameter in native mouse muscles ( Lafoux et al, 2020 ). Of note, this parameter is independent of CSA and provides a functional measurement that could be used to compare different studies regardless of the construct size or platform used.…”
Section: Contractile Force Data Analysismentioning
confidence: 93%
“…Appealing evidence shows that the TRPV1 channel plays key roles in thermosensation, oral sensation, proteasome activity, modulation of autophagy, energy homeostasis, muscle physiology, GI motility, and the release of inflammatory mediators as well as crosstalk between the immune system and sensory nervous system. 1,18- 24 In addition, the TRPV1 channel is involved in the modulation of synaptic transmission through pre-and post-synaptic mechanisms and microglia-to-neuron communication. 10 To elaborate, the TRPV1 channel modulates glutamatergic and GABAergic transmission and causes changes in neuronal firing.…”
Section: Trpv1 In Healthmentioning
confidence: 99%
“…8 Moreover, TRPV1 mutations are associated with muscle disorders such as exertional heat stroke and malignant hyperthermia. 24 Additionally, several studies have shown that TRPV1 activation leads to Ca 2+ release, membrane excitability, neurotransmitter release, and muscle contraction. 174 Supporting this contention, it has been revealed that the upregulation of nitric oxide and peroxynitrite in overloaded muscle activates the TRPV1 channel.…”
Section: Trpv1 and Disorders Of The Muscular Systemmentioning
confidence: 99%
See 1 more Smart Citation